Metabonomics Study of Ginseng Glycoproteins on Improving Sleep Quality in Mice. (3rd March 2019) - Wang, Ying; Zhu, Difu; Chen, Yinghong; Jiang, Ruizhi; Xu, Hong; Qiu, Zhidong; Liu, Da; Luo, Haoming
Abstract : The changes of brain metabolism in mice after injection of ginseng glycoproteins (GPr) were analyzed by gas chromatography mass spectrometry- (GC/MS-) based metabolomics platform. The relationship between sedative and hypnotic effects of ginseng glycoproteins and brain metabolism was discussed. Referring to pentobarbital sodium subthreshold test, we randomly divided 20 mice into two groups: control and ginseng glycoproteins group. The mice from the control group were treated with normal saline by i.p and GPr group were treated with 60 mg/kg of GPr by i.p. The results indicated that GPr could significantly improve the sleep quality of mice. Through multivariate statistical analysis, we found that there were 23 differential metabolites in whole brain tissues between the control group and the GPr group. The pathway analysis exhibited that GPr may be involved in the regulation of the pathway including purine metabolism, nicotinate and nicotinamide metabolism, glycine, serine and threonine metabolism, arginine and proline metabolism, alanine, aspartate and glutamate metabolism, and steroid hormone biosynthesis. This work is helpful to understand the biochemical mechanism of GPr on promoting sleep and lay a foundation for further development of drugs for insomnia.